2000
DOI: 10.1104/pp.123.4.1427
|View full text |Cite
|
Sign up to set email alerts
|

A Plastid Terminal Oxidase Associated with Carotenoid Desaturation during Chromoplast Differentiation

Abstract: The Arabidopsis IMMUTANS gene encodes a plastid homolog of the mitochondrial alternative oxidase, which is associated with phytoene desaturation. Upon expression in Escherichia coli, this protein confers a detectable cyanide-resistant electron transport to isolated membranes. In this assay this activity is sensitive to n-propyl-gallate, an inhibitor of the alternative oxidase. This protein appears to be a plastid terminal oxidase (PTOX) that is functionally equivalent to a quinol:oxygen oxidoreductase. This pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
184
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(203 citation statements)
references
References 33 publications
14
184
0
5
Order By: Relevance
“…Concerning regulation in leaves and seedlings, there are contradictory results. Increased psy and pds transcript levels were found in tomato seedlings treated with the PDS inhibitor norflurazon (Giuliano et al, 1993;Scolnik and Giuliano, 1994) and plants of the tomato mutant ghost bearing a mutation in the tomato gene encoding PTOX (Scolnik et al, 1987;Josse et al, 2000), indicating an end product or stress-dependant regulation. The same conclusion was made for transgenic tobacco plants having a chimeric PDS promoter/␤-glucuronidase fusion that upon norflurazon treatment yielded higher ␤-glucuronidase activity (Corona et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning regulation in leaves and seedlings, there are contradictory results. Increased psy and pds transcript levels were found in tomato seedlings treated with the PDS inhibitor norflurazon (Giuliano et al, 1993;Scolnik and Giuliano, 1994) and plants of the tomato mutant ghost bearing a mutation in the tomato gene encoding PTOX (Scolnik et al, 1987;Josse et al, 2000), indicating an end product or stress-dependant regulation. The same conclusion was made for transgenic tobacco plants having a chimeric PDS promoter/␤-glucuronidase fusion that upon norflurazon treatment yielded higher ␤-glucuronidase activity (Corona et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, levels of b-carotene, neoxanthin, and lutein, all derived from lycopene, were increased. It is also important to note that expression of ORR and genes encoding PDS, ZDS, and CRITSO are not correlated during development; while expression of ORR is reduced after the green stage, PDS, ZDS, and CRITSO show an increase in their transcript levels (Josse et al, 2000).…”
Section: Involvement Of Orr In the Carotenoid Biosynthetic Pathwaymentioning
confidence: 99%
“…Moreover, it was proposed that chlororespiration, a respiratory electron transfer chain in the thylakoids, whose functioning has been clearly established in Chlamydomonas reinhardtii (Nixon, 2000;Peltier and Cournac, 2002) could also modulate PQ pool redox status in chloroplasts of higher plants. Although it has been demonstrated that the oxidative reaction of chlororespiration involving a plastid-located terminal oxidase (PTOX; Wu et al, 1999;Carol and Kuntz, 2001) deeply affected carotenogenesis in leaves (Wu et al, 1999;Josse et al, 2000), the participation of the other reactions in modulating the redox state of PQ has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Other members of the di-iron carboxylate protein family (reviewed in Ref. 21), which all share this iron binding motif, include the ribonucleotide reductase subunit R2 (RNR), the hydroxylase subunit of methane monooxygenase (MMO), toluene monooxygenase, the acyl carrier protein ⌬ 9 fatty acid desaturase, rubrerythrin, bacterioferritin, the mitochondrial alternative oxidase (AOX) (22), and the plastid terminal (plastoquinol) oxidase (PTOX) (23). These enzymes catalyze diverse reactions but among them are found hydroxylases (MMO and toluene monooxygenase), as well as The hydroxylation of demethoxyquinone to 5-hydroxyUQ requires Coq7 in eukaryotes and many eubacteria but is catalyzed by the unrelated UbiF in E. coli.…”
Section: Identification Of Coq7 As a Di-iron Carboxylatementioning
confidence: 99%